Adapting a Cognitive Dissonance-based Eating Disorders Prevention Program for Adolescent Girls with Type 1 Diabetes. Issue 1 (2nd January 2023) - Trojanowski, Paige J.; Mehlenbeck, Robyn; Fischer, Sarah
ABSTRACT: Adolescent girls with Type 1 diabetes (T1D) are at high risk for developing eating disorders (EDs), a comorbidity that undermines treatment adherence and contributes to serious medical complications. Despite these concerns, no teen prevention programs exist that address risk factors specific to T1D. This study aimed to adapt an existing, empirically supported cognitive dissonance-based ED prevention program ( Body Project ) for teen girls with T1D. Young women with T1D, parents, and multidisciplinary medical professionals participated in semi-structured focus groups and individual interviews centered on understanding T1D-specific factors that influence body image development and eating and gathering suggestions for modifying the program to address T1D-specific factors. Multiple themes were identified related to complicating factors: diabetes stereotypes and misinformation, illness non-acceptance, demands of T1D management, adolescent-doctor relations, and family factors. Three themes related to protective factors also emerged: illness acceptance, validation and normalization of experiences, and family factors. Stakeholder feedback on program structure was also gathered. The adapted manual protocol is described in detail in addition to how findings extend current theoretical models of ED development in young women with T1D. The adapted ED prevention program, Body Project (T1D Style), centers on promoting illness acceptance, encouraging self-affirmation, teaching effective communication skills, and enhancing social support in addition to the original program's focus on challenging and resisting sociocultural appearance pressures.